Analysis of the Use of the Dana Application as a Digital Payment Tool in Facilitating Consumer Purchasing Transactions - Zebua, Wasiat Elfan Daud; Mendrofa, Yupiter; Zebua, Emanuel; Gea, Jeliswan BIJ (Manunggal Halim Jaya, 2024)
This research aims to achieve the following objectives: (1) to explore how the implementation of the DANA e-wallet facilitates consumer transactions at the Ya'ahowu Market in Gunungsitoli City; (2) to examine the usage patterns of the DANA application within the Ya'ahowu Market; and (3) to identify the challenges and risks associated with using the DANA application in simplifying transactions for consumers at the market. The research methods employed include observation, interviews, and documentation collection, with five respondents participating in the study. Based on interviews with key informants, the study found that the increasing adoption of e-wallets, such as DANA, has significantly streamlined transaction processes at Ya'ahowu Market. Informants revealed that, prior to the introduction of the DANA application, transactions were conducted solely in cash. However, since the app’s integration, both buyers and sellers at Ya'ahowu Market have embraced e-wallets, recognizing their potential to simplify transactions and enhance overall market efficiency. This shift demonstrates the market's effort to keep up with technological advancements in digital payment systems.